2007
DOI: 10.1017/s0022112007006830
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional flow of foam around a circular obstacle: local measurements of elasticity, plasticity and flow

Abstract: We investigate the two-dimensional flow of a liquid foam around circular obstacles by measuring all the local fields necessary to describe this flow: velocity, pressure, bubble deformations and rearrangements. We show how our experimental setup, a quasi-2D "liquid pool" system, is adapted to the determination of these fields: the velocity and bubble deformations are easy to measure from 2D movies, and the pressure can be measured by exploiting a specific feature of this system, a 2D effective compressibility. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
92
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 63 publications
(148 reference statements)
11
92
1
Order By: Relevance
“…In addition, k n = nπ/L is the wavenumber and ω n is the fluid-free-surface natural frequency. Using the relation (20) we obtain…”
Section: Discussionmentioning
confidence: 99%
“…In addition, k n = nπ/L is the wavenumber and ω n is the fluid-free-surface natural frequency. Using the relation (20) we obtain…”
Section: Discussionmentioning
confidence: 99%
“…[11,7,43]. Bubble distributions are monodisperse in size and disordered in geometry (shape, number of neighbors).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It had been suggested that fluctuations remain relevant even at large scale, in which case detailed statistical theories of long-range correlations and avalanches would be required [9,10]. This view is challenged by recent experiments which suggest that even these materials can be treated as continuous materials described by tensorial equations [3,11]; thus in principle partial differential equations could lead to the long-awaited predictions.…”
Section: Introductionmentioning
confidence: 99%
“…the geometrical properties of the different foams studied. Foams were produced by the "liquid-glass" technique [12,13,14], in which bubbles are blown through a nozzle in a detergent solution. Two nozzles with different diameters were used to create small and large bubbles simultaneously, with a size dispersity of about 5% in each.…”
Section: Methodsmentioning
confidence: 99%